Analysing The Effectiveness Of An Extensive Reading On Grade Eleven Students’ Reading Comprehension - Rafikah Alfiani; Tauricha Astiyandha (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
This research is about the Extensive Reading Strategy to interest Students in reading comprehension. Extensive Reading is reading as much as possible that the material of the text not be chosen by the teacher, but the students can choose the title of the books, novel by themselves. The researcher believes that this strategy can make the students more interested in learning English, especially in reading comprehension. This research did about two months in SMA PELITA TIGA NO. 3 Jakarta. The population of this research consists of 120 students sitting in four classes. The samples of the research were taken by the means of cluster random sampling from the population, class XI IPS 2 as the control class and XI IPA 1 as the experimental class, with the total sample number of 60 students consisted of 30 students each class. The adopted research methodology was quasi-experimental research, with the research design post-test only control group design. To collect data the writer used instruments of question items. The statistic method used to analyse the data was a T-test using SPSS through the testing of Null Hypotheses, which was preceded by the normality test and homogeneity test as the pre-requisite to the data analysis. The result of the test showed that H0 is rejected and Ha is accepted which proves that there is significant effect of the use of Extensive Reading on grade eleven students’ Reading Comprehension at SMA PELITA TIGA NO. 3 Jakarta in the academic year of 2019/2020.